آليات تعزيز الأمن الاقتصادي والسلم الاجتماعي: رؤية فقهية معاصرة = Mechanisms of promoting economic peace and social security: a contemporary juristic perspective - Zaroum, AbdulHamid Mohamed Ali; Abdul Wahab, Amer (Department of Fiqh and Usul Fiqh, Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2020)
يسلط هذا البحث الضوء على بعض الآليات التي تسهم في تعزيز السلم الاجتماعي والأمن الاقتصادي، وتؤدي إلى تحقيق استقرار المجتمعات، وازدهار اقتصاده، من منظور الرؤية الإسلامية المستوحاة من النصوص الشرعية ومن ممارسات الرعيل الأول الذين عاشوا بسلام ونشروا في العالم السلام. تتمثل إشكالية البحث في سؤال جوهري؛ هل للإسلام رؤية في تحقيق السلم الاجتماعي والأمن الاقتصادي؟ لقد تناول الباحث - مستقرئا آيات الكتاب المجيد، مستخدما المنهج التحليلي - هذه الآليات التي من أهمها: تحريم وتجريم الحروب وتحريم الميسر، وتقسيم المجتمع إلى طبقات، وكل ما من شأنه أن يغذّي العداوات، و يؤدي إلى تفويت مقصد الشارع من المال والثروة،. من أهم النتائج التي توصل إليها هذا البحث، أن الإسلام تشدد في تحريم الاحتكار والربح الفاحش، وأوصى بالتوزيع العادل للثروة، وعدم تكديسها في أيد قليلة، والنأي عن جمع الأرباح الهائلة من خلال استغلال حاجة المستهلك، وأن ديننا الحنيف يدعونا إلى تقريب الفوارق الاقتصادية بين الأفراد حتى لا يكون ثمة ثراء فاحش، أو فقر مدقع. ********************************************************************************* This paper highlights some of the mechanisms that contribute to the promotion of social peace and economic security and lead to the stabilization of societies and the prosperity of its economy from the Islamic perspective inspired by the Islamic text as well as the practices of the first Muslim generation who lived in peace and spread peace in the world. The primary research problem is a fundamental question: Does Islam has a vision in achieving social peace and economic security? Adapting Analytical approach, the researcher has dealt with these mechanisms the most important of which are the prohibition and criminalization of wars, the prohibition of gambling, the division of society into classes, and all that would nourish enmities. Among the most important findings of this research is that Islam strictly prohibits monopoly and obscene profit, requires equitable distribution of wealth so that it is not accumulated in a few hands and to refrain from exploiting the need of the consumer and that our religion calls us to close the economic differences among individuals so that there is no super-rich, or extreme poverty.